Faktor-Faktor yang Mempengaruhi Minat Mahasiswa Akuntansi dalam Memilih Karir sebagai Akuntan Publik - Syarief, Hanni Annisa; Boedi, Soelistijono; Syahdan, Saifhul A.; Ruwanti, Gemi (Owner : Riset dan Jurnal Akuntansi, 2024)
Currently, many companies need public accounting services, but it is difficult to find a professional accountant because the process of becoming a certified public accountant is not easy and takes a lot of time and money. Therefore, this profession is still less popular in Banjarmasin. In fact, currently there is little interest in accounting students choosing a career as a public accountant. The aim of this research is to obtain empirical evidence of the influence of financial rewards, job market considerations, work environment, family environment and professional recognition on accounting students' interest in choosing a career as a public accountant. This research is quantitative research with the population of students majoring in accounting from universities in Banjarmasin including STIE Indonesia Banjarmasin, STIE Nasional, STIE Pancasetia and the Faculty of Economics of Lambung Mangkurat University. By employing purposive sampling, 100 respondents are obtained as samples. Furthermore, the data collected from questionnaires are analyzed by using multiple linear regression analysis method. The research results show that financial rewards, work environment, and professional recognition have a positive and significant effect on accounting students' interest in choosing a career as a public accountant in Banjarmasin. Meanwhile, considerations of the job market and family environment do not influence accounting students' interest in choosing a career as a public accountant in Banjarmasin.